Bird diversity in six habitat types of PT Inhutani I Labanan, East Kalimantan (Biodiversitas Journal of Biological Diversity, 2016)
Birds can be used indirectly or directly as a bioindicator of environment. Birds species living in six habitat types of PTInhutani I Labanan Kalimantan Timur (namely, logged-over areas that has been exploited in 1976/1981 and 1981/1986,forested area that is being exploited in 1999/2000, primary forest that will be exploited in 2001/2002, Labanan Jaya Villageinhabited in 1982/1983, and Segah-Malinau Transmigration Settlement inhabited in 1997/1998) were recorded with transectmethod (long of 3 km and within sighting distance of 25-50 m) at 06.30-10.00 and 15.00-17.30 in both dry and rainy seasons. One hundred and two identified species belonging to 34 families and 6 unidentified species were found. Habitat types and seasons affect bird diversity (the number of species and abundance). Percent dissimilarity of birds between habitats ranged 0,53-0,95 in rainy season and 0,54-0,95 in dry season and between seasons ranged 0,50-0,80. Quantitative values have to be completed with qualitative consideration to assess habitat condition or changes.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: bird diversity, forest, urban area, habitat condition.